2020
DOI: 10.46810/tdfd.822928
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Pollen Extract Mediated Gold Nanostructures

Abstract: There is an increasing demand in the synthesis of shape and size-controlled gold nanostructures (Au NSs) with greener methods. Therefore, we aimed to synthesize differently shaped and sized Au NSs using a greener technique under ambient conditions. In this study, we utilized pollen extracts of Corylus avellana, Juniperus oxycedrus and Pinus nigra species (collected from Kastamonu region of Turkey) for the synthesis. The extraction was performed in water in order to recover "water soluble" content from the poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 42 publications
(55 reference statements)
0
14
1
Order By: Relevance
“…ChemistrySelect DPPH-based antioxidant activity of the plant extracts doesn't have correlation with the speed of nanostructure formation, which was shown for pollen extracts as well. [11] In contrast to our findings, Stozhko et al (2019) reported a comparative study using three different plant sources and showed the electrochemically determined antioxidant activity gave a relationship with the characteristics of AuNSs. Their findings showed that higher antioxidant capacity provides smaller and more stable AuNSs.…”
Section: Chemistryselectcontrasting
confidence: 99%
See 2 more Smart Citations
“…ChemistrySelect DPPH-based antioxidant activity of the plant extracts doesn't have correlation with the speed of nanostructure formation, which was shown for pollen extracts as well. [11] In contrast to our findings, Stozhko et al (2019) reported a comparative study using three different plant sources and showed the electrochemically determined antioxidant activity gave a relationship with the characteristics of AuNSs. Their findings showed that higher antioxidant capacity provides smaller and more stable AuNSs.…”
Section: Chemistryselectcontrasting
confidence: 99%
“…Particularly, plant extracts provide synthesis of unique shaped and sized MNSs. [10][11][12] In addition to the green synthesis, plant extracts synthesized MNSs carry a variety of bioactive compounds that bring out charming potentials for biological applications, including regulation of cell metabolism. [13] Plant extracts contain a variety of phenolic compounds that play role in the synthesis MNSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,3,4] Extraction methods play the key roles in isolation of the targeted compounds, and it is known that aqueous extraction allows collection of water-soluble compounds that can be used in the synthesis of inorganic nanomaterials that don't require further surface modification to be hydrophilic. [5,6] This is important for the synthesis of greener or even green inorganic nanomaterials. However, there is a major problem to develop reproducible inorganic nanomaterials with the use of the plant parts, which resulted from the lack of knowledge about the chemical composition of the extract.…”
Section: Introductionmentioning
confidence: 99%
“…The pollen grains were either used as a template, substrate or source of organic pool in the synthesis of silver nanostructures, cerium oxide nanoemulsions, gold nanostructures and magnetic nanoparticles. [2,[6][7][8][9][10] Even though pollen grain extracts are most widely used to synthesize pollen grain mediated INSs, there is no information how the extract chemistry contributes to the formed INSs morphology and size. Therefore, in this study, nine different pollen extracts were used to synthesize gold nanostructures (AuNSs) to understand how the chemical composition alter the size and morphology.…”
Section: Introductionmentioning
confidence: 99%